2016
DOI: 10.1515/botcro-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Early Spring Flora of the Sub-Pannonic Steppic Grassland (NATURA 2000 Site) in Bilje, Northeast Croatia

Abstract: -The diversity of early spring vascular fl ora was studied in the Sub-Pannonic steppic grassland in the village of Bilje, north eastern Croatia. In all, 109 plant taxa within 35 families were found. The highest number of taxa belongs to the families Poaceae, Fabaceae, Asteraceae, Caryophyllaceae, Lamiaceae and Rosaceae. Specifi c habitat conditions, characterized by moderately wet and moderately acidic soil with intermediate fertility and the effects of the continental climate favour the development of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The field detection of flora units from this study indicated an increase in the population count of endangered flora species, with the number of detected flora units increasing to 129 as compared with 109 units five years prior [7]. To potentially extend their habitat to neighboring areas, we proposed a habitat suitability prediction method based on noninvasive field observations from remote sensing imaginh using a UAS multispectral camera system and machine learning classification.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The field detection of flora units from this study indicated an increase in the population count of endangered flora species, with the number of detected flora units increasing to 129 as compared with 109 units five years prior [7]. To potentially extend their habitat to neighboring areas, we proposed a habitat suitability prediction method based on noninvasive field observations from remote sensing imaginh using a UAS multispectral camera system and machine learning classification.…”
Section: Discussionmentioning
confidence: 93%
“…The steppe in Bilje is located in the central part of a cemetery and covers an area of 0.63 ha, representing the last remnant of the steppe-like grassland in Croatia (Figure 1). There is a significant share of the xerothermic elements from the eastern European steppes, for which this study area represents a westernmost limit of distribution [7]. Research in the past thirty years has confirmed that there were more such habitats in eastern Croatia but they have mostly disappeared due to land-use transformation into arable land or overgrowing with shrubs [10].…”
Section: Study Area and Fieldworkmentioning
confidence: 99%
See 2 more Smart Citations